A clinically relevant murine model unmasks a "two‐hit" mechanism for reactivation and dissemination of cytomegalovirus after kidney transplant. Issue 9 (14th May 2019) - Zhang, Zheng; Qiu, Longhui; Yan, Shixian; Wang, Jiao‐Jing; Thomas, Paul M.; Kandpal, Manoj; Zhao, Lihui; Iovane, Andre; Liu, Xue‐feng; Thorp, Edward B.; Chen, Qing; Hummel, Mary; et al.
Abstract : Reactivation of latent cytomegalovirus remains an important complication after transplant. Although immunosuppression (IS) has been implicated as a primary cause, we have previously shown that the implantation response of a kidney allograft can lead to early transcriptional activation of latent murine cytomegalovirus (MCMV) genes in an immune‐competent host and to MCMV reactivation and dissemination to other organs in a genetically immune‐deficient recipient. We now describe a model that allows us to separately analyze the impact of the implantation effect vs that of a clinically relevant IS regimen. Treatment with IS of latently infected mice alone does not induce viral reactivation, but transplant of latently infected allogeneic kidneys combined with IS facilitates MCMV reactivation in the graft and dissemination to other organs. The IS regimen effectively dampens allo‐immune inflammatory pathways and depletes recipient anti‐MCMV but does not affect ischemia–reperfusion injury pathways. MCMV reactivation similar to that seen in allogeneic transplants combined with also occurs after syngeneic transplants. Thus, our data strongly suggest that while ischemia‐reperfusion injury of the implanted graft is sufficient and necessary to initiate transcriptional reactivation of latent MCMV ("first hit"), IS is permissive to the first hit and facilitates dissemination to other organs ("second hit"). Abstract : In a murine model of kidney transplant, ischemia–reperfusion injury serves as a 'first hit' that initiates transcriptional reactivation of latent CMV, while immunosuppression provides a 'second hit, ' facilitating dissemination of CMV to other organs. See the editorial by Cook onpage 2399 .